Removal of Pb2+ metal ion using electrolysis system of Fe(s)/NaCl(aq), Pb(NO3)2(aq)//H2O(aq)/C(s). (April 2020) - Suyati, L; Efendi, D; Gunawan, G; Haris, A; Widodo, D S
Abstract: Lead 2+ is very dangerous heavy metal for the environment due to its toxicity and it requires a serious handling. A more efficient and effective method for handling is electrolysis using electrocoagulation. This method provides an electric current to the system, a redox reaction occurs followed by a coogulation process, which then absorbs Pb 2 + metal ions to form flocculants. the study covered electrocoagulation of artificial waste containing Pb 2+, characterization of functional groups and compounds contained in flocculants. The two compartment reactor was used. It consisted of an anode (iron) and cathode (graphite) parts separated by a salt bridge. The anode was filled with 0.1M NaCl electrolyte solution, artificial waste of Pb(NO3 )2 . The cathode contained H2 O. Potential was set in the range of 1-6 V. Then the filtrate at the anode was analyzed by AAS and the precipitate was characterized by FTIR and SEM EDX. The results showed Pb metal waste was removed 43.2% by electrocoagulation method at a maximum voltage of 6 V. FITR result shows Fe-O in the wave numbers of 1117 and 111.99 cm −1 and Pb-O in the wave numbers of 482.22 and 474.82 cm −1 . SEM analysis shows that the morphology has slightly changes. Elements contained by EDX analysis of the floc are iron, lead, oxygen, silica and sodium.